E-Cigarettes: Perceptions, Buying Interest and Opportunities - Azzahra, Naftali; Maidah, Liko; Khansa, Nabila; Erawati, Dedet (Indonesian Journal of Multidisciplinary Science, 2025)
E-cigarettes have now begun to be positively accepted by the public, especially among adolescents and young adults, as an alternative that is considered safer than conventional cigarettes. This study explores the perception, purchase intention, and market opportunity of e-cigarettes in Cirebon City using a descriptive qualitative approach. Data were collected through in-depth interviews with health experts, e-cigarette users, and vape businesses. Theory Planned Behavior (TPB) and Theory Diffusion of Innovations (DOI) were used to analyze factors influencing the adoption of e-cigarettes. The results showed that people's perceptions of e-cigarettes varied, influenced by health, social, and economic factors. Purchase intention is influenced by price, product variety, and the influence of the social environment. From a business perspective, e-cigarettes have vast market opportunities, but face regulatory challenges. This study provides insights for stakeholders in understanding the dynamics of the e-cigarette market as well as related policy implications.